IMPROVING HEALTHY LIFESTYLE COMPLIANCE IN AGRICULTURAL COMMUNITIES THROUGH THE AGRONURSING MODEL: AN EXPERIMENTAL STUDY - Astuti, Anggia; Fibriansari, Rizeki Dwi; Abidin, Zainal (Universitas Aisyah Pringsewu, 2025)
Background : Agricultural workers are often overlooked, facing health risks such as pesticide exposure, poor dietary choices, and limited physical activity, which increase their vulnerability to chronic diseases. Psychosocial factors, including stress from uncertain crop yields and adverse weather, also contribute to mental health issues like anxiety and depression. This complex health landscape necessitates effective healthcare approaches that integrate traditional and contemporary systems to address both physical and mental health challenges. Aim: This study aims to evaluate the effectiveness of the Agronursing Model, which combines agronomy and nursing principles, in improving healthy lifestyle adherence among agricultural workers, ultimately enhancing their overall well-being. Method: An experimental quantitative method was employed, utilizing a descriptive analysis and survey approach to assess a Healthy Lifestyle Education intervention among 250 farmers in the Sukodono Health Center Working area, Lumajang Regency. Respondents were recruited through probability sampling, with data collected via questionnaires and observation sheets focusing on healthy lifestyle compliance. Results: The intervention resulted in notable improvements in activity patterns, dietary habits, and rest quality, demonstrating its positive impact. Enhancements included increased physical activity, better dietary adherence, reduced fatigue, and decreased financial anxiety and work-related stress.